Monetary and Exchange Rate Arrangements for Nafta - Eichengreen, Barry (IMF Working Papers; Working Paper ;, 1993)
This paper considers the extent to which the North American Free Trade Area (NAFTA) meets the criteria for a common currency area. NAFTA is compared with the EC, a regional grouping for which initial plans for a monetary union are already in place. Most of the anticipated benefits from a monetary union in the EC apply with equal force to NAFTA. However, because the underlying disturbances are more diverse across members of NAFTA, the costs of abandoning the exchange rate instrument are likely to be higher. This is particularly true when NAFTA is compared to the EC's continental core.